2003
DOI: 10.1038/sj.bmt.1703808
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-leukaemia effect in children: chronic GVHD has a significant impact on relapse and survival

Abstract: Summary:To examine whether graft-versus-host-disease (GVHD) is associated with a graft-versus-leukaemia (GVL) effect that also influences the outcome of allogeneic stem cell transplantation (SCT) in childhood acute leukaemia, we evaluated all consecutive (n ¼ 169) children who had undergone SCT for ALL and AML at our centre. Median followup was 7 years. The 5-year probability of chronic GVHD was 34%. Median time to relapse was 24 months in children with chronic GVHD and 6 months in those without. The correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…A select number of studies have shown an impact of acute 10, 34, 35 or cGvHD 11, 36 on relapse after related or unrelated bone marrow HSCT for pediatric acute leukemia. Pulsipher et al observed that aGvHD and pre-transplant MRD, independently and in combination, influenced the risk of relapse after HSCT for pediatric ALL after controlling for graft source and other variables 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A select number of studies have shown an impact of acute 10, 34, 35 or cGvHD 11, 36 on relapse after related or unrelated bone marrow HSCT for pediatric acute leukemia. Pulsipher et al observed that aGvHD and pre-transplant MRD, independently and in combination, influenced the risk of relapse after HSCT for pediatric ALL after controlling for graft source and other variables 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the GvL effect, likely due to immune surveillance provided by donor NK- and T-cells, is important in eradicating leukemia after allogeneic HSCT 25 , although the GvL effect in ALL may be weaker than in other malignancies 6–8 . Select clinical reports have demonstrated lower rates of relapse in pediatric patients with ALL who experience graft-versus-host disease (GvHD) after HSCT, providing indirect evidence of GvL actions in this disease 911 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of aGVHD in ALL has been less clearly defined than the generally accepted notion that the GVL effect plays an important role in the treatment of AML. Many recent publications (Zecca et al , ; Gustafsson Jernberg et al , ; Nordlander et al , ) have reported the effects of GVHD and GVL on remission rates and OS for acute leukaemic relapse after SCT in both adult and paediatric populations. This indicates that the GVL effect may also improve the ALL survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of chronic GvHD is lower in children but remains significant. A review of the experience of a single centre, which evaluated patients transplanted for leukaemia using several different regimens for GvHD prophylaxis, had a chronic GvHD rate of 34% (Gustafsson Jernberg et al , 2003). A recent evaluation of GvHD following matched sibling or one antigen mismatched‐related transplantation by the Children's Cancer Group, in which GvHD prophylaxis was uniform, reported a chronic GvHD rate of 21·2% with 7·3% of the patients with limited disease and the remaining 14% demonstrating extensive disease (Neudorf et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to modulate the immune system frequently result in GvHD that may improve disease‐free survival (DFS) but result in chronic GvHD. Long‐term follow‐up of adults and children increasingly demonstrate a possible role for chronic GvHD in improving DFS, especially in high‐risk malignancies, but may not improve event‐free survival (EFS) secondary to complications of GvHD and its treatment (Cutler et al , 2001; Gustafsson Jernberg et al , 2003; Neudorf et al , 2004). The recent publication by the Children's Cancer Group demonstrated the benefit of acute GvHD in relapse‐free survival (Neudorf et al , 2004), while the role of chronic GvHD in children has been reported from Sweden (Gustafsson Jernberg et al , 2003).…”
Section: Introductionmentioning
confidence: 99%